Development of Heat Source for Performance Verification of Thermal Management for Double-Sided Cooled SiC-Power Semi-conductors - Cepin, Simon; Borcherding, Holger (PCIM Europe 2023; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)
In this paper a research process to verify thermal management for double-sided cooled SiC-power semiconductors will be discussed. In the context of previous researches a high performance cooling system for these semiconductors was developed. In many cases, prototypes of power semiconductors are used in research projects. This often leads to the fact that only small numbers are available or that they are not available right from the start. Close cooperation with semiconductor manufacturers, like Infineon Technologies AG in this case, within these projects offers the opportunity to get information about the internal structure of the semiconductors and their packages. This information, the use of special PCB manufacturing methods, as well as thermal simulation are used to build up a heat source that mimics the semiconductor including the package and thus gives us the opportunity to verify the performance of our thermal management for high integrated power electronics.